Reaction of the Phytochemistry Community to Green Chemistry: Insights Obtained Since 1990 - Funari, Cristiano S. [UNESP]; Rinaldo, Daniel [UNESP]; Bolzani, Vanderlan S. [UNESP]; Verpoorte, Robert (American Chemical Society (ACS), 2023)
This review article aims to study how phytochemists have reacted to green chemistry insights since 1990, the year when the U.S. Environmental Protection Agency launched the “Pollution Prevention Act”. For each year in the period 1990 to 2019, three highly cited phytochemistry papers that provided enough information about the experimental procedures utilized were sampled. The “greenness” of these procedures was assessed, particularly for the use of solvents. The highly hazardous diethyl ether, benzene, and carbon tetrachloride did not appear in the papers sampled after 2010. Advances in terms of sustainability were observed mainly in the extraction stage. Similar progress was not observed in purification procedures, where chloroform, dichloromethane, and hexane regularly have been employed. Since replacing such solvents in purification procedures should be a major goal, potential alternative approaches are discussed. Moreover, some current initiatives toward a more sustainable phytochemical research considering aspects other than only solvents are highlighted. Although some advances have been achieved, it is believed that natural products chemists can play a major role in developing a novel ecological paradigm in chemistry. To contribute to this objective, six principles for performing natural products chemistry consistent with the guidelines of green chemistry are proposed.